Revised Ordinances of the Corporation of Winchester, with the Act of Incorporation and Certain Other Acts of the General Assembly Concerning the Town of Winchester, and the Constitution of Virginia, at 78, Ordinance no. 21, § 3 (1856) - (:unkn) unknown (My University, 1856)
Any person who shall fire a gun, pistol or other firearm within this Corporation, except in case of necessity in the discharge of a public duty, or at military parade by order of the officer in command, shall for each offense forfeit the sum of one dollar.
Keywords: DISCHARGE